2019
DOI: 10.1016/j.dib.2019.104722
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic data of the microbial community of lab-scale nitritation-anammox sequencing-batch bioreactor performing nitrogen removal from synthetic wastewater

Abstract: The nitritation-anammox process, which involves partial aerobic oxidation of the ammonium to nitrite and following oxidation of ammonium by nitrite to molecular nitrogen, is an efficient and cost-effective approach for biological nitrogen removal from wastewater. To characterize the microbial communities involved in the nitrogen and carbon cycles in wastewater treatment bioreactors employing this process, we sequenced the metagenome of a sludge sample collected from the lab-scale nitritation-anammox sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In more detail, we used two data sets from rivers, River1 ( https://www.ncbi.nlm.nih.gov/sra/?term=ERR466320 ) and River2 ( 37 ), one from the seagrass rhizosphere ( 38 ), one from the skin ( 39 ), one from the stool ( 40 ), one from the soil ( 41 ), one from thermal pools ( 42 ), and three from bioreactors (Bioreactor1 [ 43 ], Bioreactor2 [ 44 ], and Bioreactor3 [ 44 ]). Nine of the 10 data sets consist of short reads, whereas the last data set consists of ONT MinION long reads.…”
Section: Methodsmentioning
confidence: 99%
“…In more detail, we used two data sets from rivers, River1 ( https://www.ncbi.nlm.nih.gov/sra/?term=ERR466320 ) and River2 ( 37 ), one from the seagrass rhizosphere ( 38 ), one from the skin ( 39 ), one from the stool ( 40 ), one from the soil ( 41 ), one from thermal pools ( 42 ), and three from bioreactors (Bioreactor1 [ 43 ], Bioreactor2 [ 44 ], and Bioreactor3 [ 44 ]). Nine of the 10 data sets consist of short reads, whereas the last data set consists of ONT MinION long reads.…”
Section: Methodsmentioning
confidence: 99%
“…The medium composition and preparation are described in Kallistova et al (2020). An activated sludge containing anammox bacteria (Mardanov et al, 2019a) was used as an inoculum for the reactors' first run. One liter of the inoculum with a total suspended solid content of 3.8 g/l was added to 3.5 L of the medium to start each reactor.…”
Section: Setup Configuration and Operationmentioning
confidence: 99%
“…Chloroflexi, UTCFX1 is anaerolineae bacterium that commonly detected in active sludge from anaerobic digesters and SBR in WWTPs 269 270 . Although the ecological role of the Anaerolineae remains uncertain due to the scarcity of isolates and annotated genome sequences, recent studies found the evidence of its ability of carbohydrate fermentation 270 . Bacteria of Acidobacteria phylum carry carbon metabolism-associated genes involved in the degradation of polysaccharides and aromatic compounds 271 .…”
Section: Recommendations For Future Researchmentioning
confidence: 99%